2020
DOI: 10.3390/nu12040894
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perceptions of Women from Under-Resourced South African Communities about Participating in a Low-Carbohydrate High-Fat Nutrition and Health Education Program: A Qualitative Focus Group Study

Abstract: Scientific evidence suggests that low-carbohydrate high-fat (LCHF) diets may be effective for managing non-communicable diseases (NCDs). Eat Better South Africa (EBSA) is an organization that runs LCHF nutrition education programs for women from low-income communities. Three focus group discussions (FGDs) were held with 18 women who had taken part in an EBSA program between 2015 and 2017, to explore their perceptions and to identify the facilitators and barriers they faced in implementing and sustaining dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Additionally, after completing the JBI critical appraisal on the remaining articles, the reviewers determined all studies had low to moderate risk of bias and decided to move forward with the eligible studies (see Appendix B for detailed summary of appraisal results). Therefore, the present review is based on the results of 13 articles: eight cross sectional studies (Allen et al, 2018; Ambwani et al, 2020; Condon et al, 2007; Eisenberg et al, 2005; Grigg et al, 1996; Marquez et al, 2018; Maxwell et al, 2017; Worsley and Skrzypiec, 1997), three qualitative studies (Poirier et al, 2016; Pujol-Busquets et al, 2020; Rydén and Sydner, 2011), one cohort study (Bonaccio et al, 2012), and one non-randomized experimental study (Paxton et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, after completing the JBI critical appraisal on the remaining articles, the reviewers determined all studies had low to moderate risk of bias and decided to move forward with the eligible studies (see Appendix B for detailed summary of appraisal results). Therefore, the present review is based on the results of 13 articles: eight cross sectional studies (Allen et al, 2018; Ambwani et al, 2020; Condon et al, 2007; Eisenberg et al, 2005; Grigg et al, 1996; Marquez et al, 2018; Maxwell et al, 2017; Worsley and Skrzypiec, 1997), three qualitative studies (Poirier et al, 2016; Pujol-Busquets et al, 2020; Rydén and Sydner, 2011), one cohort study (Bonaccio et al, 2012), and one non-randomized experimental study (Paxton et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes ranged from 14 participants to 2337 with eight of the studies consisting solely of female participants (e.g. Eisenberg et al, 2005; Pujol-Busquets et al, 2020) and only one study had a majority of male participants (Maxwell et al, 2017). There was a large distribution of mean age ranges among studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative and survey research has shown that adults consuming a low-carbohydrate eating pattern have positive health outcomes such as less hunger, greater energy, and improved health, but that lack of support from family and physicians can be a barrier to adherence [161,162]. Qualitative surveys of healthcare providers reveals that many practitioners have found low-carbohydrate diets to be helpful for their patients and as a consequence, have changed the way they view and practice healthcare [163].…”
Section: Qualitative Researchmentioning
confidence: 99%